Mystical Sense and Literal Sense in Nahmanides’ Commentary on the Book of Job (Doctor Virtualis, 2024)
Nahmanides’ Commentary on the Book of Job constitutes an ideal anthropological and eschatological corollary of his monumental Commentary on the Torah. A leading figure of the Girona’s Jewish community and of its kabbalistic school, where the teachings of the Provençal master Isaac the Blind were enriched with elements of the Talmudic, Hellenistic and Arabic traditions, Nahmanides outlines a kabbalistic esoteric interpretation of Job designed to reject the seeming ontological irreconcilability between the individual experience of suffering and the ordered system of a universe forged in the demiurgic night of the origins. After explaining, in allusive language and midrashic style, the nature of human soul and the origin of evil, Nahmanides proves that Job’s protest, the protest of a just man suffering unjustly, is nothing but a dissonance destined to resolve itself into the superior harmony of the creation. This is the great mystery of individual existence, a mystery that echoes in the silence of Job, warned by God, and that unveils itself only to those initiates who, like Elihu critic of Job and of his three friends, who are merely short-sighted consolers, have been chosen as depositaries of the most ancient wisdom.
Keywords: Nahmanides; Job; eschatology; exegesis; metempsychosis; Kabbalah